CHARACTER BUILDING THROUGH TRADITIONAL DANCE AS DEVELOPING IDENTITY BELONGINGS: A STUDY OF INDONESIA-MALAYSIA - Nerosti Adnan (International Conference on Languages and Arts, 2014)
The tittle above shows that if a person learns a traditional dance of a specific community, they unconsciously learn about the culture and the moral values of the community too, which is beneficial to them. According to Hughes (2009), the learning process of traditional dance covers four different learning’s ethics: (1) discipline; (2) courtesy and respect; (3) socialize and not arrogant; (4) consistency and confidence. This four ethics can be analyzed in an integrated manner on the textual and contextual of a traditional dance. Among other things: dancing is actually a skill capability that will not be achieved without strong discipline to practice continuously. Salam hormatin the form of squat’s motion, both hands brought together in front of the chest or in the direction of the guest (organized into ten fingers) as initiating a traditional dance. This act is actually to educate the polite nature and mutual respect toward each other. Empirically, dance can be used as a medium of learning in the intimate and socialize formations. The beauty of dance itself can be achieved with simultaneous movement or uniform. Every motion that made by the whole body is the vision of the intellectual character’s build, discipline, art and spiritual, creative and fear of God. So that, the process that must be undertaken in learning a dance is not just memorizing the movement of the dance as a text, but the dancers need to keep planting the values of it in their life.  It is importance as it helps to led the process of personality’s formation which is guide to responsibility and sharing to achieve the goal to always be independent and have their own true identity.   Keywords: Character’s Development, Traditional Dance, Dance Lessons, True Identity